Upaya Perlindungan Anak Melalui Pelayanan Shelter Anak : Studi Deskriptif Rumah Peduli Anak Tenaga Kerja Indonesia - Susilowati, Dyah; Cholid, Sofyan (UI Scholars Hub, 2014)
This research discussed about the efforts of child protection through the implementation of shelter children service at Rumah Peduli Anak Tenaga Kerja Indonesia (RPA-TKI). The purpose of this research is to describe on the protection of and services provided by RPA-TKI to children who are vulnerable to the TKI neglect and child trafficking. This research is qualitative research with the kind of descriptive research. The results of this research described that the service which is provided by RPA-TKI is child protection services in the form of children’s shelter in order to meet the basic needs of TKI’s children. The service of the children’s shelter which is served by RPA-TKI is going well although it has not implemented the manual standard of children’s shelter